Who spends and who does not: Clustering visitors at a national arts festival - M. Saayman; A. Saayman; E. Slabbert (South African Journal of Business Management, 2011)
The Grahamstown National Arts Festival is the oldest National Arts Festival in South Africa and was founded in 1974. This celebration of the arts takes place over a period of eleven days with the main festival running over eight days, which also makes it the longest (in terms of number of days) arts festival in the country. The literature review revealed that high spenders at arts festivals are also the visitors who buy the most show tickets. The success of these events is determined by ticket sales and not necessarily by the number of visitors. Therefore, the purpose of this paper is to determine who the high spenders at the Grahamstown National Arts Festival are. Data obtained during the festival in 2008 by means of a questionnaire survey (N=446) was statistically analysed by means of K-means clustering, Pearson‟s chi-square test and ANOVAs. Results indicated two clusters, namely high and low spenders and can assist festival organisers in developing a more focused marketing strategy and festival programme. This was the first time that K-means clustering was applied to festival data in South Africa.
Keywords: 650